The Effects of Peer Education on The Behaviors Regarding HIV/AIDS Transmission Prevention Among Street Children in Bandung City - Meilianingsih, Lia; Setiawan, Ridwan; Sofyana, Haris (Health Notions, 2017)
All adolescents are vulnerable to HIV/AIDS, including street children. The behaviors of street children are much influenced by their peers. Peer education can enhance knowledge, attitudes, beliefs, and skills and empower children to be responsible for protecting the health of themselves and their peers (Wahyuni, 2012). This study aims to determine the effects of peer health education on the HIV/AIDS Preventive Behaviors of Street Children in Bandung City in 2015. The research employed a quasi-experimental method with the pre-post-test control group design. The sample was 26 people for the treatment group and 26 people for the control group, respectively, taken with purposive sampling technique. Interventions began with peer educator training and then the peer educators provided health education on HIV/AIDS transmission prevention through small group discussions for 2 days. The data in this study were not normally distributed. The paired or dependent data were analyzed using the Wilcoxon test, while the unpaired or independent data using Mann-Whitney test. The results of the research show that peer health education had effects on the knowledge and attitudes of the street children (p values 0.00 and 0.00, respectively); however, there was no effect of peer health education on the actions regarding HIV/AIDS transmission prevention among the street children (p value 0.09). Hence, it is advisable to conduct health promotion with peer health education method in an effort of increasing knowledge and attitudes regarding HIV/AIDS transmission prevention among street children that is sustainable and integrated with the existing programs at puskesmas (Community Health Center).